Adopting the Development of Course Delivery Approach towards Active Learning Based on the Utilization of Technology and Web Based Accounting Education - Amahi, Amahi (Journal of Education and Vocational Research, 2014)
Over the years, accounting students and lecturers have been grappling with the challenges of achieving better results arising from the traditional approach of teaching which is passive, and lecture and lecturer – centred. This has not been very effective as the traditional course delivery mode or approach is being adopted. As the world is becoming a global village, it demands/requires new and improved methods to enhance students needed skills, competencies and knowledge expected of them by employers and modern day technologically equipped offices. The paper focuses on information and web based technologies in teaching accounting courses and their usefulness in improving students learning. The mean, standard deviation and t – test was used to analyse the data e generated in the study. The findings show that Information and Web Based Technologies would be relevant and bring about individualized student learning, enhance understanding, better skill and competencies acquisition and ensure accurate record retrieval for the global world and would be the basis for curriculum review and retraining of teachers for better course delivery based on Information and Web Based Technologies.